Analisis Beban Kerja Perawat Rawat Inap Di Indonesia Pasca Pandemi Covid19: Literature Review - Faatin, Aliefah Nur; Ilyas, Jaslis (Syntax Literate, 2025)
COVID-19 pandemic has significantly increased the workload of nurses in inpatient units at government hospitals in Indonesia. Despite the end of the pandemic status, current reports indicate that nurse workload remains high due to service complexity, nurse-to-patient ratio imbalance, and growing administrative and psychosocial demands. This study is a systematic literature review aimed at analyzing the current state of inpatient nurse workload in Indonesian government hospitals post-COVID-19. Literature was sourced from Google Scholar, Garuda, and Scopus using Boolean syntax tailored to each database. Nine primary studies from 2023 to 2025 met the inclusion criteria. Results revealed that nurse workload remains high, driven by inadequate staffing, increased non-clinical duties, and work-related stress. Workload assessment methods varied, including FTE (Full-Time Equivalent), Ministry of Health standards, NASA-TLX (Task Load Index), and self-report surveys. Findings show that high workload negatively affects job satisfaction, competence, and increases the risk of burnout. In contrast, hospitals with equitable task distribution and strong organizational support report lighter workloads. This review concludes that a combined approach to workload assessment is essential, and data-driven workload management strategies are needed to enhance service quality and nurse well-being.